The effect of object-valence relations on automatic evaluation - Moran, Tal; Bar-Anan, Yoav (Cognition and emotion, 2013)
Two experiments tested the effect of co-occurrence of a target object with affective stimuli on automatic evaluation of the target when the relation between the target and the affective stimuli suggests that they have opposite valence. Participants learned about targets that ended an unpleasant noise or a pleasant music. The valence of such targets is opposite to the valence of the affective stimuli that co-occur with them. Participants reported preference for targets that ended noise over targets that ended music, but automatic evaluation measures revealed the opposite preference. This suggests that automatic evaluation is sensitive to co-occurrence between stimuli more than to the relation between the stimuli, and that relational information has a stronger influence on deliberate evaluation than on automatic evaluation. These conclusions support the associative-propositional evaluation model (Gawronski & Bodenhausen, 2006), and add evidence regarding the sensitivity of the evaluative-conditioning effect to relational information.